Lo poético cinematográfico : la imagen luciérnaga de Gustavo S. Fontán - Martins, Laura M. (ACC : Department of Foreign Languages and Literatures at North Carolina State University, 2022)
"'The cinematographic poetic: the firefly image of Gustavo S. Fontán' is part of the growing interest in the forms that 'the poetic' adopts in cinema. Within the current panorama of Argentine cinema, Fontán stands out for building a consistent trajectory in the desire to scrutinize the materiality of the world and move away from the serialized models of the standardized rhetoric of the late-capitalist market (his films constitute 'works without a place'). It reveals to us the possibility of enjoying the concrete (perhaps a way of learning to live in another way) and forges a warp that is poetic--and pictorial--with its own 'tempo' that allows us to contemplate and repair the 'enigmatic proliferation of matter that we call the world'. He invites us to appreciate iridescence, blurred contours, opacities, presences and fleeting moments, which enables us to value the modesty with which he gives us each visual and sound image. Fontán tries to reconfigure the space of the senses, arouse emotions with cognitive capacity, expand the limits of what can be experienced and open up new auditory worlds for us based on that kind of foreign language that is his cinema"-- Provided by publisher.
Keywords: Fontán Merlino, Gustavo -- Criticism and interpretation.; Motion picture producers and directors -- Argentina.; Motion pictures -- Production and direction -- Argentina.; Motion pictures -- Argentina -- History.; Producteurs et réalisateurs de cinéma -- Argentine.; Cinéma -- Production et réalisation -- Argentine.; Cinéma -- Argentine -- Histoire.; Motion picture producers and directors; Motion pictures; Motion pictures -- Production and direction; Argentina; Criticism, interpretation, etc.; History